2021
DOI: 10.3390/ijms22052517
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Adenoviruses for Cancer Therapy

Abstract: Many immuno-therapeutic strategies are currently being developed to fight cancer. In this scenario, oncolytic adenoviruses (Onc.Ads) have an interesting role for their peculiar tumor selectivity, safety, and transgene-delivery capability. The major strength of the Onc.Ads is the extraordinary immunogenicity that leads to a strong T-cell response, which, together with the possibility of the delivery of a therapeutic transgene, could be more effective than current strategies. In this review, we travel in the ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…Another vaccination method is based on non-replicating adenoviral vectors. Adenoviruses (Ads) are an ideal vector candidate for SARS-CoV-2 vaccines due to their capacity to infect target cells and express transgene at a high level [69]. Furthermore, the Ads-mediated infection can induce the upregulation of costimulatory molecules that stimulate the cytokine and chemokine responses with a consequent improvement of the immune response [70].…”
Section: A Race For a Covid19 Vaccinementioning
confidence: 99%
“…Another vaccination method is based on non-replicating adenoviral vectors. Adenoviruses (Ads) are an ideal vector candidate for SARS-CoV-2 vaccines due to their capacity to infect target cells and express transgene at a high level [69]. Furthermore, the Ads-mediated infection can induce the upregulation of costimulatory molecules that stimulate the cytokine and chemokine responses with a consequent improvement of the immune response [70].…”
Section: A Race For a Covid19 Vaccinementioning
confidence: 99%
“…Each of these exemplar fields of nanoparticle studies, which are reviewed in greater depth below, have characteristic differences that can be exploited and utilized for novel oncotherapeutic generation. [21], (B) liposomes [22], and (C) exosomes [23]; oncolytic viruses: (D) adenovirus [24], (E) herpes virus [25], and (F) vaccinia virus [26]; (G) oncolytic bacteria: G. Salmonella [27], (H) vegetative Clostridium [28], and (I) Clostridium spore [28].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Oncolytic viral therapy utilizes genetically modified viruses capable of selective replication in tumor cells to mediate oncotherapy (Figure 1D-F) [24,25,70,[73][74][75]. Unfortunately, early studies used unattenuated viruses with potent toxicities, almost ubiquitously resulting in severe-often fatal-adverse events [76], which not only halted on-going studies, but have had lasting impacts-stunting the development and translation of this technology [77].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The clear importance of NK cells in controlling both anti-viral and anti-cancer responses indicated that modulation of NK cell activities has the potential to promote the OV efficacy. OVs have been developed from a range of different virus families [ 4 ], including herpesvirus [ 46 ], reovirus [ 47 ], polio virus [ 48 ], parvovirus [ 49 ], vaccinia [ 50 ] and adenovirus [ 51 ]. These viruses have vastly different structures, lifecycles, tropisms and toxicities, and induce variable immune responses that could influence the efficacy in different settings [ 52 , 53 ].…”
Section: Natural Killer (Nk) Cell Responses In the Context Of Ovmentioning
confidence: 99%